2006
DOI: 10.1007/s00784-006-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and surface characterization of two self-etching adhesive systems and a total-etch adhesive after bonding to ground and unground bovine enamel—a qualitative study

Abstract: The purpose of the study was to evaluate the enamel surface and interface morphology of two self-etching adhesive systems (SAS) vs a total-etch control, after bonding to ground and unground enamel using field emission scanning electron microscopy (FESEM). Thirty bovine incisors were used in this study. The buccal enamel surface of 15 teeth was ground flat to resemble freshly cut enamel. The rest of the teeth were left intact. Two SAS, Clearfil SE Bond (CSE, Kuraray) and Prompt L-Pop (3M-ESPE), and a convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…3 Relevant data indicate that the depth of the resin tag penetration increases when the enamel is etched with 35% phosphoric acid than when enamel is conditioned with self-etching primers. [8][9][10][11][12] The present study was undertaken to test the null hypothesis that there is no difference in the colour change of enamel after finishing following the removal of brackets bonded by different bonding protocols. The association between colour change and lengths of remnant resin tags was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Relevant data indicate that the depth of the resin tag penetration increases when the enamel is etched with 35% phosphoric acid than when enamel is conditioned with self-etching primers. [8][9][10][11][12] The present study was undertaken to test the null hypothesis that there is no difference in the colour change of enamel after finishing following the removal of brackets bonded by different bonding protocols. The association between colour change and lengths of remnant resin tags was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This property has shown to result in reduced degradation of mechanical properties during water storage, thus resulting in no significant reduction in the bond strength of the adhesive over time. The superior performance of etch‐and‐rinse adhesive is due to formation of longer microresin tags within enamel, resulting in a scalloped interface which in turn makes it more resistant to crack propagation and hence better retention of the sealant; however, in this study, the retention of the sealant in etch‐and‐rinse group was significantly higher only at a short‐term follow‐up (3 months). Thus, in spite of better bonding mechanism, there was loss of bonding over time, due to exposure to masticatory and thermal stresses.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study, it was concluded that pH is not the only parameter necessary for achieving a good bond. 32 Ibarra et al 33 evaluated the enamel surface and interface morphology of self-etch and etch-and-rinse adhesives after bonding to ground and unground enamel. They did not observe large differences between ground and unground enamel surfaces either in their surface etching effect or in the ultrastructural morphology of the adhesive interface.…”
Section: Discussionmentioning
confidence: 99%